Long lifespans have evolved with long and monounsaturated fatty acids in birds. (24th September 2015) - Galván, Ismael; Naudí, Alba; Erritzøe, Johannes; Møller, Anders P.; Barja, Gustavo; Pamplona, Reinald
<x xml:space="preserve">Abstract</x> The evolution of lifespan is a central question in evolutionary biology, begging the question why there is so large variation among taxa. Specifically, a central quest is to unravel proximate causes of ageing. Here, we show that the degree of unsaturation of liver fatty acids predicts maximum lifespan in 107 bird species. In these birds, the degree of fatty acid unsaturation is positively related to maximum lifespan across species. This is due to a positive effect of monounsaturated fatty acid content, while polyunsaturated fatty acid content negatively correlates with maximum lifespan. Furthermore, fatty acid chain length unsuspectedly increases with maximum lifespan independently of degree of unsaturation. These findings tune theories on the proximate causes of ageing while providing evidence that the evolution of lifespan in birds occurs in association with fatty acid profiles. This suggests that studies of proximate and ultimate questions may facilitate our understanding of these central evolutionary questions.